Core Java SE 9 for the impatient - Horstmann, Cay S., 1959- (Addison-Wesley, 2018)
"Readers familiar with Horstmann's original, two-volume "Core Java" books who are looking for a comprehensive, but condensed guide to all of the new features and functions of Java SE 9 will learn how these new features impact the language and core libraries. Instead of the meticulous detail that the much larger two-volume set provides, this condensed treatment focuses on practical examples and is presented in bite-sized chunks. As with Java 8, Modern Java idioms are no longer required and there is a much faster, easier pathway for learning Java. Horstmann quickly cuts to the chase without lecturing about the superiority of one paradigm over another or rehashing Java history. Given the size of the Java language and the scope of the new features introduced in Java 9, there is a great deal of new material to cover, but it is presented in small chunks organized so that you can quickly retrieve it when needed. This book covers all aspects of Java that a modern developer needs to know, including modularity, as well as the powerful lambda expressions that were introduced in Java 8. It will also tell you how to find out more about old-fashioned concepts that you might still see in legacy code, but won't dwell on them" -- Provided by publisher.